Enhancing coulombic efficiency and rate capability of high capacity lithium excess layered oxide cathode material by electrocatalysis of nanogold. Issue 24 (18th February 2016) - Ma, Quanxin; Mu, Deying; Liu, Yuanlong; Yin, Shibo; Dai, Changsong
Abstract : A lithium-rich cathode material Li1.2 Mn0.56 Ni0.16 Co0.08 O2 modified with nanogold (Au@LMNCO) for lithium-ion (Li-ion) batteries was prepared using co-precipitation, solid-state reaction and surface treatment techniques. Abstract : A Lithium-rich cathode material Li1.2 Mn0.56 Ni0.16 Co0.08 O2 modified with nanogold (Au@LMNCO) for lithium-ion (Li-ion) batteries was prepared using co-precipitation, solid-state reaction and surface treatment techniques. Au@LMNCO was prepared by thermally spraying gold on the surface of the lithium-rich cathode material (LMNCO). X-ray diffraction (XRD) and energy dispersive spectrometry (EDS) results indicate that Au was successfully integrated into the surface of LMNCO. The cyclic voltammogram of Au@LMNCO shows a significant reduction in the reaction overpotential compared to that of LMNCO, which was a result of the nanogold formation. The stable reversible capacity of the Au@LMNCO electrode was 249 mA h g −1, and it could be retained at 244 mA h g −1 (98% retention) after 100 cycles at 0.5C. The coulombic efficiencies were over 98% except for the first five cycles. Moreover, Au@LMNCO also exhibited excellent rate capability. Even at a 5.0C rate, its discharge capacity was about 190 mA h g −1 . The superior electrochemical performance can be attributed to its unique nanoplate characteristics, its structural stability, and the electrocatalytic activity of nanogold.